Using Digital Promotion Tools As A Mean To Improve The Brand Image Study Of Sofitel Algiers Hamma Garden Hotel During The Second Six-month Period Of 2023 - Gherbal Chahinda; Dridi Ahlem (جامعة الوادي University of Eloued, 2024)
The present study aims to identify the extent to which digital promotion tools (website, email, social networking sites, digital advertising, search engines, digital content creation) contribute to improving the brand’s image. We have chosen the Sofitel Hotel, Algiers, for the case study. The study included a sample of employees in the hotel under study. We relied on the interview as a tool for collecting data, and we analyzed that data following a qualitative approach. This study reached several results, the most important of which are: there is a contribution of digital promotion tools to improving the brand image of the Sofitel Hotel Algiers, as the latter applies digital promotion strategies. One of the most important research recommendations is that the sofitel Hotel should explore opportunities for cooperation with digital influencers in the field.
Keywords: digital marketing; brand image; digital mail; digital website; social networking sites; search engines